A neuromuscular‐based analysis of the open payments program. Issue 1 (3rd August 2020) - Harada, Yohei; Sheng, Sen; Thombre, Vaishali A.; Ounpraseuth, Songthip; Tommee, Carolina Gil; Annapureddy, Amarnath R.; Kamran, Mudassar; Jasti, Madhu S.; Katsuno, Masahisa; Yadala, Sisira; Veerapaneni, Karthika; Kapoor, Nidhi; et al.
Abstract: Introduction: In August 2013, the Centers for Medicare and Medicaid Services (CMS) Open Payments Program (OPP) made eligible payment information publicly available. Data about industry payments to neuromuscular neurologists are lacking. Method: Financial relationships were investigated between industry and US neuromuscular neurologists from January 2014 through December 2018 using the CMS OPP database. Results: The total annual payments increased more than 6‐fold during the study period. The top 10% of physician‐beneficiaries collected 80% to 90% of total industry payments except in 2014. In 2018, the most common drugs associated with payments to neuromuscular neurologists were nusinersen, vortioxetine, eteplirsen, alglucosidase alpha, edaravone, and intravenous immunoglobulin. Discussion: A substantial increase in the annual payments to neuromuscular physicians during the study period is likely due to the development of new treatments, including gene therapy. Abstract : See Editorial on pages 5–6 in this issue .